The Psychology of Addictive Smartphone Behavior in Young Adults: Problematic Use, Social Anxiety, and Depressive Stress - Pera, Aurel (Frontiers in Psychiatry, 2020)
This review enhances the existing literature on relationships between problematic smartphone use (PSU), psychopathology, addictive personality, and online social engagement as regards young adults, giving attention to predictive determinants of addictive behavior in smartphone usage. My article cumulates previous research findings on the psychology of addictive smartphone behavior in terms of problematic use, social anxiety, and depressive stress by focusing on the relationship among mobile social media usage, smartphone addiction risk, mental health issues, and individual well-being. The inspected collected findings prove that depression and social anxiety constitute risk determinants for greater PSU and that particular categories of smartphone applications are positively related to well-being. State anxiety and motivations represent significant predictors of PSU. High PSU affects participation in social engagement. As limitations in the current review, my results point towards relevant avenues of research on social consequences of teenagers’ smartphone problematic use. Future directions should clarify whether compulsive smartphone use adversely affects both mental and physical health in the long run.